2015
DOI: 10.1177/0046958015609607
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Awareness of the Affordable Care Act and Application Assistance Among Low-Income Adults in Three Southern States

Abstract: The Affordable Care Act (ACA) expanded Medicaid eligibility to adults with incomes under 138% of the federal poverty level, leading to substantial reductions in uninsured rates among low-income adults. Despite large gains in coverage, studies suggest that Latinos may be less likely than other racial/ethnic groups to apply and enroll in health insurance, and they remain the group with the highest uninsured rate in the United States. We explore two potential factors related to racial/ethnic differences in ACA en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…28 Latino patients have been found to have less awareness of the ACA than the general population. 29 Furthermore, studies within the past 5 years have documented socioeconomic disparities in knowledge of basic concepts of health insurance. 3033 An American Life Panel survey reported that approximately 30% of persons with an income at or below the federal poverty limit could correctly describe a deductible.…”
Section: Discussionmentioning
confidence: 99%
“…28 Latino patients have been found to have less awareness of the ACA than the general population. 29 Furthermore, studies within the past 5 years have documented socioeconomic disparities in knowledge of basic concepts of health insurance. 3033 An American Life Panel survey reported that approximately 30% of persons with an income at or below the federal poverty limit could correctly describe a deductible.…”
Section: Discussionmentioning
confidence: 99%
“…; Derose and Baker 2000; Fiscella et al . ; Mosqueira, Hua, and Sommers ; Sanchez ; Sanchez and Morales ; Stephens and Artiga ; Valdez et al . ; Wallace et al .…”
Section: Public Policy As a Social Determinant Of Healthmentioning
confidence: 99%
“…These barriers to accessing health care include income inequalities (Clark et al. ), low levels of awareness of the ACA (Garcia Mosqueira, Hua, and Sommers ), and language proficiency and other health system barriers (Ortega, Rodriguez, and Vargas Bustamante ). Focusing on this specific eligible population, we were able to examine the differential effects of the expansion on health access and racial/ethnic disparities.…”
mentioning
confidence: 99%